Mission to Siam : the memoirs of Jessie MacKinnon Hartzell - Hartzell, Jessie MacKinnon, 1884-1968 (University of Hawaiʻi Press, 2001)
"Jessie MacKinnon Hartzell arrived in Northern Thailand in 1912, the young wife of a recently ordained Presbyterian missionary. Thousands of miles lay between her and her grandparents' farm in Nova Scotia, where she had been born and raised. But over the next sixteen years, Thailand became her beloved new home. She was awed by its physical beauty - the great rivers, the orchid-studded hills - and became devoted to its people. Beginning as a nurse, she eventually directed a small hospital. There she discovered her talent for organization and hard work. She also found, to her grief, that her work separated her from her children." "Mission to Siam casts unexpected light on colonialism, the Asia missions, and the convulsive changes that a newly united Thailand underwent in the early twentieth century. It is a significant contribution to the handful of published works that describe firsthand the experience of women missionaries. This is a heartfelt account by a strong, intelligent woman caught between what she owed her family and what she felt she owed herself: a calling, a career, an adventure."--Jacket